Concise Review: Markers for Assessing Human Stem Cell-Derived Implants as β-Cell Replacement in Type 1 Diabetes. (5th July 2016) - Pipeleers, Daniel; Robert, Thomas; De Mesmaeker, Ines; Ling, Zhidong
Abstract : : A depleted β-cell mass causes diabetes complications that cannot be avoided by insulin administration. β-Cell replacement can stop their development when restoring insulin's homeostatic role. This requires a sufficient number and an adequate functional state of the β cells, together defined as "functional β-cell mass." Intraportal implants of human pancreatic islet cells correct hyperglycemia in patients with type 1 diabetes, but this effect is transient and often incomplete. Studies to improve outcome are hindered by shortage in donor pancreases. Human pluripotent stem cells are a candidate source for mass production of grafts for β-cell replacement. Their in vitro differentiation to pancreatic endoderm (stage 4) and to β-cell-containing preparations (stage 7) provides grafts that generate β-cell implants in mice. In vivo markers indicated a better outcome of device-encapsulated stage 4 cells and microencapsulated stage 7 cells as compared with nonencapsulated grafts. Encapsulation also offers the advantage of representative implant retrieval for direct analysis by ex vivo markers. Combination of in vitro, in vivo, and ex vivo markers allows comparison of different stem cell-derived grafts and implants, with each other and with clinical islet cell preparations that serve as reference. Data in mice provide insights into the biology of stem cell-generated β-cell implants, in particular their capacity to establish and sustain a functional β-cell mass. They can thus be indicative for translation of a graft to similar studies in patients, where metabolic benefit will be an additional marker of primordial importance. Significance : Human stem cell-derived preparations can generate insulin-producing implants in immune-incompetent mice. Steps are undertaken for translation to patients with type 1 diabetes. Their therapeutic significance will depend on their capacity to establish a functional β-cell mass that provides metabolic benefit. This study proposes the combined use of in vitro, in vivo, and ex vivo markers to assess this potential in preclinical models and in clinical studies. Abstract : Human stem cell-derived preparations can generate insulin-producing implants in immune-incompetent mice. This study proposes the combined use of in vitro, in vivo, and ex vivo markers to evaluate the implants as beta cell replacement therapy. They can be translated to clinical studies after validation in preclinical models.